2021
DOI: 10.1002/anie.202011384
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Layer π‐Stacked Molecules as Efficient Thermally Activated Delayed Fluorescence Emitters

Abstract: Multi-layer p-stacked emitters based on spatially confined donor/acceptor/donor (D/A/D) patterns have been developed to achieve high-efficiency thermally activated delayed fluorescence (TADF). In this case, dual donor moieties and a single acceptor moiety are introduced to form two threedimensional (3D) emitters, DM-BD1 and DM-BD2, which rely on spatial charge transfer (CT). Owing to the enforced face-to-face D/A/D pattern, effective CT interactions are realized, which lead to high photoluminescence quantum yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 114 publications
(5 reference statements)
5
70
0
Order By: Relevance
“…However, spiro‐type TADF molecules containing through space charge transfer (TSCT) process [13] normally suffer from obvious device efficiency roll‐off. Quite recently, great progresses have been made by Jiang and Liao's group [10b, 13a,d–f] . Via a parallel surface strategy, TSCT process is successfully enhanced and some devices exhibit EQE max over 20 % with low efficiency roll‐off [10b, 13a,e,f,i] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, spiro‐type TADF molecules containing through space charge transfer (TSCT) process [13] normally suffer from obvious device efficiency roll‐off. Quite recently, great progresses have been made by Jiang and Liao's group [10b, 13a,d–f] . Via a parallel surface strategy, TSCT process is successfully enhanced and some devices exhibit EQE max over 20 % with low efficiency roll‐off [10b, 13a,e,f,i] .…”
Section: Figurementioning
confidence: 99%
“…Quite recently, great progresses have been made by Jiang and Liao's group [10b, 13a,d–f] . Via a parallel surface strategy, TSCT process is successfully enhanced and some devices exhibit EQE max over 20 % with low efficiency roll‐off [10b, 13a,e,f,i] . However, this type of TADF molecules usually display greenish emission, efficient TSCT based TADF molecule with blue emission still remains scarce.…”
Section: Figurementioning
confidence: 99%
“…In stark contrast to Cz, iminodibenzyl (IDB) and iminostilbene (ISB), which are C 2 -inserted homologues of Cz, [4] have been much less explored as electron donors in D-A twisted type organic functional materials. [5][6][7] In 2018, Dias and Grazulevicius reported that the attachment of ISB and IDB donors to quinoxaline acceptor unit allows unique mechanochromic luminescence properties and dual TADF and roomtemperature phosphorescence (RTP). [5] Independently, Bryce and Monkman investigated the influence of introducing ISB donor onto the 9,9-dimethylthioxanthene-S,S-dioxide (TXO2) acceptor unit on the structure and TADF properties of the D-A-D compounds in comparison with other analogous donors, thus suggesting the importance of conformations in blue TADF.…”
Section: Introductionmentioning
confidence: 99%
“…[6] They showcased that IDB donor lies between diphenylamine and dihydroacridine donors in terms of electron-donating ability and conformational flexibility. And recently, Kaji and coworkers disclosed the utilization of IDB in through-space charge-transfer (TSCT) TADF [7] material which is featured with very efficient reverse intersystem crossing (rISC). [8] Nevertheless, any other systematic studies of the influence of the C 2 insertion into the Cz unit on the physicochemical properties of D-A type compounds have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance the intra-TSCT effect, the multiple π-stacked TADF emitters DM-BD1 and DM-BD2 (Figure 17e), featuring the donor-acceptor-donor 3D scaffold linked by the two fluorenyl units, were developed. [109] The calculated ΔE ST s Adachi's group designed and synthesized the spirobased TADF emitter QAFCN where the rigid donor 5,9-dihydroquinolino[3,2,1-de]acridine displayed the deformed configuration (Figure 18). [110] It was supposed that the greatly shortened spatial separation between the donor and the acceptor would further promote the intra-TSCT.…”
Section: Stacked and Cofacial Donor-acceptor Pairs Induced Intra-tsctmentioning
confidence: 99%